How to Simulate Galactic Outflows?. Issue Volume 10:Issue S309(2014) (9th February 2015) - Barai, Paramita
Abstract: A challenge in cosmological simulations is to formulate a physical model of star-formation (SF) and supernovae (SN) feedback which produces galactic outflows like that widely observed. In several models an outflow velocity ( v out ) and mass loading factor (η) are input to the sub-resolution recipe. We present results from our MUPPI model, which uses local properties of gas, and is able to develop galactic outflows whose properties correlate with global galaxy properties, consistent with observations; demonstrating a significant improvement in such work.